Concept Analysis of Kalinaw among Cebuano Speakers Using Kawakita Jiro Method - Padilla, Joseph E.; Padilla, Corazon A. (Center of Language and Cultural Studies [CLCS], 2021)
The way people think and perceive things significantly affects their view of the world and their behavior towards it. To gain a deeper understanding of how they construct and interpret meanings, it is imperative to examine how people build and associate a particular concept. In this study, the researchers delved into people’s perception and understanding of the concept of Kalinaw which is a Cebuano term associated with the English word peace. Responses of 100 conveniently selected participants from a researcher-made questionnaire were listed, tallied, and ranked. Moreover, the researchers utilized Kawakita Jiro (KJ) Analysis as a framework to determine relationships of coded items by sorting and clustering based on their relatedness, similarities, and connection to construct themes and sub-themes. Results show that kalinaw is understood as 1) internal, external, relational, and spiritual manifestations, 2) internal and external state of being, and 3) natural, social, self, spatial, temporal, and situational context. This suggests that people’s concept of kalinaw is relative to the varying areas or contexts and is constructed by the combination of multiple social factors at the individual, social, spiritual, political, environmental, and cultural levels.